CHEMICAL ANALYTICAL APPROACHES OF DETERMINATION OF CONTENT OF CHLOROHYDROCARBONS AND THEIR METABOLITES IN BIOLOGICAL MATRIXES - O. M. Zhurba; S. F. Shayakhmetov; A. N. Alexeyenko (Acta Biomedica Scientifica, 2012)
Improving of methodical approaches to gas chromatography methodologies of determination, of chlorohydrocarbons — vinyl chloride, 1,2-dichloroethane — and their metabolites — chloroethanol, monochloroacetic acid, and. thiodiglycolic acid. — in biological matrixes (blood and. urine) is reviewed. Metrological characteristics were determined. Content of these chemical compounds and. their metabolites in biological matrixes of workers contacting with chlorohydrocarbons was studied.